Pengaruh Penerapan Program Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan Bagian Produksi PT. Djitoe Indonesian Tobacco Surakarta - Supono, Endro, Dwi Astuti, SKM.,M.Kes, Sri Darnoto, SKM.,M.Kes (2017)
The implementation of K3 in the company is very important because it provides protection against work accidents and prevent heavy losses for the company, as well as improving employee motivation in work. The purpose of this research is to know the influence of the K3 programs on performance of employees part of the production of PT Djitoe Indonesia Tobacco Surakarta. Research conducted with observational who use cross sectional approach. Sample research with purposive sampling of as many as 47 samples. Statistical tests using test correlation chi square with computer programs. Research results application of occupational health and safety program mostly with either category of 22 respondents (46,8%), the majority of respondents in the category of high performance of 20 respondents (42.6%). There was significant influence between the HSE performance with employees (p < 0.001), where the higher level programs K3, then the higher performance levels of employees.